Analisis Determinan Ekspor Nikel di Indonesia: Studi Kasus Sebelum dan Sesudah Kebijakan Pelarangan Ekspor - Fadiya Khansazalfa; Karuniana Dianta Arfiando Sebayang; Dicky Iranto (Indo Publishing, 2026)
This study analyzes the determinants of nickel exports in Indonesia before and after the implementation of the export ban policy. Using time series data from 2014 to 2025 (48 quarterly observations), this research employs multiple linear regression analysis with the Ordinary Least Square (OLS) method and Newey-West Heteroskedasticity and Autocorrelation Consistent (HAC) standard errors to address autocorrelation issues. The dependent variable is nickel export value, while the independent variables are capital goods (proxied by mining machinery imports), exchange rate (USD/IDR), and the export ban policy as a dummy variable. The results show that the exchange rate has a positive and significant effect on nickel exports (t-statistic = 4.789; p = 0.000), and the export ban policy has a positive and significant effect (t-statistic = 3.254; p = 0.002). However, capital goods do not have a significant effect on nickel exports (t-statistic = -0.230; p = 0.819). The adjusted R-squared value of 85.53% indicates that the three independent variables explain most of the variation in nickel exports. These findings confirm that exchange rate depreciation and downstreaming policies are key drivers of Indonesia's nickel export performance, while upstream mining machinery imports have not yet contributed significantly to export growth